The Andean Group: An answer to some problems of LAFTA - Sven Heldt (Institut für Weltwirtschaft (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1972)
Regional economic integration is considered as an efficient mean to accelerate economic development of the participating states. It is therefore one of the major themes of the next UNCTAD conference. One famous example of integration between developing countries is LAFTA (Latin American Free Trade Association). LAFTA failed, however, in so far as the smaller members were not able to achieve the gains in industrial development they had hoped for. This seems to have been due to the fact that LAFTA mainly concentrated on trade liberalization. An answer to these shortcomings is the Andean Group, formed by Bolivia, Chile, Colombia, Ecuador, and Peru. The Group tries to solve the problems through implementation of sectorial programs of industrial development and a harmonized investment policy. The Andean Group is therefore a unique example where trial and error lead to a new and possibly more adequate form of economic integration.
Keywords: 330